ANALYSIS OF THE IMPACT OF FINANCIAL TECHNOLOGY (FINTECH) ON THE INDONESIAN ECONOMY IN THE NEW NORMAL ERA - Yuni Utami (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the impact of Financial Technology (Fintech) on the Indonesian economy in the new normal era. This study uses a quantitative approach with time series data in the form of monthly Fintech statistical reports from June 2020 to June 2022 and monthly SEKI (Indonesian Economic and Financial Statistics) reports from June 2020 to June 2022. The analysis technique of this research uses regression. The results of this study indicate that Fintech has a positive and significant impact on Indonesia's economic growth. This shows that the faster Fintech growth in Indonesia, the more positive the impact on the Indonesian economy. These results implicitly state that one of the ways to improve the Indonesian economy in the New Normal Era is by increasing Fintech.